2020
DOI: 10.1002/casp.2480
|View full text |Cite
|
Sign up to set email alerts
|

Can regenerated inner‐city areas remain sites of public‐place sociability? Psycho‐social processes predicting public sociability in a changing neighbourhood

Abstract: The processes of urban regeneration of long‐disinvested inner‐city neighbourhoods today happening in many European cities sometimes dramatically transform residents' traditional uses of their public places. Focusing on a neighbourhood renowned for its traditional public place sociability – Mouraria, in Lisbon – this study explored the psychosocial processes that may shape the maintenance of that sociability in the face of increasing social diversification and small‐scale gentrification brought about by a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
(124 reference statements)
1
0
0
Order By: Relevance
“…Another contribution of this study is related to the functions of spaces. Consistent with the recent social psychology literature (Bettencourt, Castro, & Dixon, 2021), we found that the history of the spaces and knowledge about the spaces play a vital role in the identity processes of residents. However, instead of considering spaces as contested between groups and intergroup conflict (Dixon et al, 2020), our study adds to the literature by suggesting that spaces are a basis for collective action.…”
Section: Discussionsupporting
confidence: 90%
“…Another contribution of this study is related to the functions of spaces. Consistent with the recent social psychology literature (Bettencourt, Castro, & Dixon, 2021), we found that the history of the spaces and knowledge about the spaces play a vital role in the identity processes of residents. However, instead of considering spaces as contested between groups and intergroup conflict (Dixon et al, 2020), our study adds to the literature by suggesting that spaces are a basis for collective action.…”
Section: Discussionsupporting
confidence: 90%